2020
DOI: 10.1007/s12665-020-09206-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impacts of land use/land cover change on the water balance in the afforested River Basin, Pakistan

Abstract: Land use and land cover (LULC) change is one of the key driving elements responsible for altering the hydrology of a watershed. In this study, we investigated the spatio-temporal LULC changes between 2001 and 2018 and their impacts on the water balance of the Jhelum River Basin. The Soil and Water Assessment Tool (SWAT) was used to analyze the impacts on water yield (WY) and evapotranspiration (ET). The model was calibrated and validated with discharge data between 1995 and 2005 and then simulated with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…In several studies, SWAT is distinctively utilized for investigating the impacts of LULC change on hydrological processes in small and large watersheds [21][22][23]. It is also commonly used for modelling and analyzing hydrological processes in the context of changing LULC and land management, with high efficiency [24].…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, SWAT is distinctively utilized for investigating the impacts of LULC change on hydrological processes in small and large watersheds [21][22][23]. It is also commonly used for modelling and analyzing hydrological processes in the context of changing LULC and land management, with high efficiency [24].…”
Section: Introductionmentioning
confidence: 99%
“…The results of five GCMs under both RCPs 4.5 and RCP 8.5 scenarios, illustrates that the change in temperature and precipitation frequencies will affect the water resources and streamflow within the transboundary, directly or indirectly. Besides climate change, other anthropogenic changes can also have a significant impact on streamflow, such as future management practices and land-use change significantly influencing water availability [61,73].…”
Section: Discussionmentioning
confidence: 99%
“…The total forest area in the entire province of KP was calculated as 10,123 km 2 using the GFW data set for 2019. The following study by Saddique et al [95] used Landsat TM, Landsat ETM+, and Landsat OLI to map the evergreen and deciduous forests in the river Jhelum basin (Mangal Dam watershed), AJK (33,397 km 2 area). Using a machine-learning algorithm (RF) in supervised image classification, they reported that the forest area showed a positive difference of 2806.87 km 2 between 2001-2009 and 2009-2018.…”
Section: Other Districtsmentioning
confidence: 99%
“…Saddique et al [95] published a study that used a machine learning algorithm (RF) to report overall accuracy of 90%, 92%, and 95%, and kappa coefficient of 89%, 90%, and 94% for 2001, 2009, and 2018. The producer's accuracy was calculated as >83%, >88%, and 93%, and the user's accuracy was calculated as >83%, >82%, and >94% for the same years, respectively.…”
Section: Accuracies Assessments and Validations For Forest Mappingmentioning
confidence: 99%